The Future of Big Data and Artificial Intelligence in Talent Management Practices: A Literature Review - Aditya Santoso; Suryono Efendi; Andini Nurwulandari (International Journal of Economics and Management Sciences, 2024)
Currently, the business sector has entered a digital transformation stage involving Big Data (BD) and Artificial Intelligence (AI). At this stage the institution must change the way it operates its business, even to a philosophical point. This paper attempts to predict the direction of these changes through literature studies. The purpose of this paper is to provide a broad view regarding the application of BD and AI in Talent Management (MT) practice. From this study it was found that the use of AI and BD in the MT process (recruiting, developing, retaining and deploying talent) has obstacles inculde: 1) availability of expert human resources, 2) data security and 3) psychological barriers of top management and employees. Some of the strategic recommendations found include: 1) Building HR expertise and adaptation, 2) Legal readiness, 3) Managerial strategy and 4) Reducing AI bias to increase the fairness of AI decisions.